The impact of physical workplace environment toward employees’ productivity: a case study of Felda Global Ventures Holdings Berhad / Muhammad Azzim Mohd Razali and Ain Sakinah Zulkifli - Mohd Razali, Muhammad Azzim; Zulkifli, Ain Sakinah (Faculty of Business and Management, 2014)
The workplace environment now plays an important part towards the employee’s itself. Every employee’s will consider these factors before they took the job on whether the workplace environment at work will meet their requirement and satisfaction or not. This is because every employee’s will require a good and comfortable workplace to enhance their productivity level. The quality of the workplace itself can determine whether the employees will stay motivated and inspired while at work. Hence, it is a crucial factor that should be taken seriously by the employer in order to retain their employees from resigning. Meanwhile the study will be conducted at FELDA GLOBAL VENTURES GLOBAL HOLDINGS BERHAD (FGV) and examines the impact of workplace environment affecting the employee’s productivity. A total of 165 questionnaires was handed out in order to collect data.